Предмет: Алгебра,
автор: незнаюкакэто8760
помогите с решить домашнюю
Приложения:
Ответы
Автор ответа:
0
общий знаменатель
(x +1)(x -1)
(2x(x -1) +(x +1)(x +1)) /(x-1)(x+1) =(2x² -2x +x² +2x +1) / (x-1)(x+1) =(3x² +1) /(x² -1)
(x +1)(x -1)
(2x(x -1) +(x +1)(x +1)) /(x-1)(x+1) =(2x² -2x +x² +2x +1) / (x-1)(x+1) =(3x² +1) /(x² -1)
Похожие вопросы
Предмет: Қазақ тiлi,
автор: balnurmusabek
Предмет: Математика,
автор: elifkaramova87
Предмет: Қазақ тiлi,
автор: kokenovaari
Предмет: Математика,
автор: allasedavnyh